PENUNTUN PRAKTIKUM PERKEMBANGBIAKAN TUMBUHAN SECARA VEGETATIF BERBASIS KONTEKSTUAL UNTUK SISWA IX SMA/MA: STUDI PENDAHULUAN DAN VALIDITAS (Universitas PGRI Sumatera Barat, 2022)
The purpose of this research is to produce practical guides that are accordance with the learning needs on vegetative plant breeding topics in IX grade ofJunior High School. Guidance development is carried out using the ADDIE models, is analysis, design, develop. The research was conducted at the PGRI Sumatera Barat University and also MTsN 2 Lima Puluh Kota District. Validity was assessed by a validity questionnaire with a Likert scale to 3 validators. Data processing is done in a quantitative way using the percentage formula by Riduwan (2013).The aspects that are assessed in the development of practicum guides are aspects of the appropriateness of the content, language, presentation, and graphics.The results of the validation obtained are very valid (90% on average) with an assessment position for the content feasibility aspect of 91%, language 85%, presentation 92%, and graphics 91%. Based on these results it can be concluded that the contextual-based practicum guide on vegetative plant propagation material developed is valid so that it can be used in the learning process